Sistem Pakar Diagnosa Penyakit Kulit Kucing Menggunakan Metode Naive Bayes Berbasis Web - Farhan Dwiramadhan; Mohammad Iwan Wahyuddin; Deny Hidayatullah (KITA Institute, 2022)
This study aims to implement the Naive Bayes method in a skin disease diagnosis system in cats. The Naive Bayes method in this application system uses disease probability calculations, calculates the probability of symptoms, calculates the posterior probability of disease, and calculates the maximum value of each disease. This method is used to analyze the results of the diagnosis of skin diseases in cats based on the symptoms of skin diseases. Data analysis on this application system is based on the results of tests carried out 50 times to produce disease diagnosis results from the user and calculated by the system to produce the same diagnostic results as calculations performed manually. With this facility, cat owners can provide first aid to help their cat before being taken to the clinic and further examined by a veterinarian.